Lukács on Uncritical Theory - Salem, A. (Sociologija. Mintis ir veiksmas, 2017)
The critique of bourgeois theory found in the work of the Marxist philosopher Georg Lukács is predicated on his argument that no part of capitalist society is free from the effects of a generalized reification, and primarily intellectual activity is very much included in the accusation. In these circumstances, if philosophical and scientific theories are blind to what lies beneath or beyond them, it is because their historically transcendent constructions reflect and reinforce the commodification that is constitutive of all of bourgeois society – economic, political, social and cultural. This article seeks to bring out the detail of these associations as they affect different types of theoretical writing at different times, from Cartesian and Kantian views through positivist science to a good deal of Marxist theory itself.